The role of social support in adult women´s weight loss: A Literature review - Martínez-Jaikel, Tatiana (RESPYN Revista Salud Pública y Nutrición, 2019)
Abstract Introduction: Excess body weight, is a worldwide health problem. Social support may play a central role during weight loss processes; however, this relationship has not been clearly established. Objective: To determine the role of social support in adult women´s weight loss. Methods: We conducted a systematic review searching four databases: PubMed, Ebsco Medline with full text, PsycINFO, and Web of Science; and including articles that were 1) related to at least one of the research question; 2) intervention studies aiming to evaluate the effectiveness of the familiar social support component in weight loss; 3) the population of the study was adult women between 18 and 65 years. Results: Ten studies relating family social support to weight loss: only a few of them have shown an association between weight loss and family social support, and none of the studies found an association between family social support and BMI; involving family members in weight loss programs seems to have some positive effect but the results are mixed. Limitations: Studies used different definitions and measures to evaluate family social support; some of them were excluded because they did not differentiate in their analysis between men and women. Conclusions: It seems to be a positive effect between social support and weight loss in women, but more studies are necessary to draw solid conclusions. Resumen: Introducción: El exceso de peso corporal, es un problema de salud mundial. El apoyo social podría jugar un papel central durante los procesos de pérdida de peso, sin embargo, esta relación no está claramente establecida. Objetivo: Determinar el papel del apoyo social en la pérdida de peso de las mujeres adultas. Métodos: Realizamos una revisión sistemática buscando cuatro bases de datos: PubMed, Ebsco Medline con texto completo, PsycINFO y Web of Science; e incluyendo artículos que fueron 1) relacionados con al menos una de las preguntas de investigación; 2) estudios de intervención con el objetivo de evaluar la efectividad del componente de apoyo social familiar en la pérdida de peso; 3) la población del estudio eran mujeres adultas entre 18 y 65 años. Resultados: Se encontraron diez estudios que relacionan el apoyo social familiar con la pérdida de peso: solo algunos de ellos demostraron una asociación entre la pérdida de peso y el apoyo social familiar, y ninguno encontró una asociación entre el apoyo social familiar y IMC; involucrar a miembros de la familia en programas de pérdida de peso parece tener algún efecto positivo pero los resultados fueron mixtos. Limitaciones: los estudios utilizaron diferentes definiciones y medidas para evaluar el apoyo social familiar; algunos de ellos fueron excluidos porque no diferenciaron en su análisis entre hombres y mujeres. Conclusiones: Parece existir un efecto positivo entre el apoyo social y la pérdida de peso en las mujeres, pero se necesitan más estudios para establecer conclusiones sólidas.